High diversity of methanotrophic bacteria in geothermal soils affected by high methane fluxes - D’Alessandro, W; GAGLIANO, Antonina Lisa; QUATRINI, Paola; PARELLO, Francesco (Copernicus GmbH (Copernicus Publications) on behalf of the European Geosciences Union (EGU)., 2014)
Volcanic and geothermal systems emit endogenous gases by widespread degassing from soils, including CH4, a greenhouse gas 25 times as potent as CO2. Recently, it has been demonstrated that volcanic/geothermal soils act as source, but also as biological filter for methane release to the atmosphere. For long time, volcanic/geothermal soils has been considered inhospitable for methanotrophic microorganisms, but new extremophile methanotrophs belonging to Verrucomicrobia were identified in three different areas (Pozzuoli, Italy; Hell’s Gate, New Zealand; Kamchatka, Russia), explaining anomalous behaviours in methane leakages of several geothermal/volcanic sites. Our aim was to increase the knowledge of the relationship between methane emissions from volcanic/geothermal areas and biological methane oxidation, by investigating a geothermal site of Pantelleria island (Italy). Pantelleria Island hosts a high enthalpy geothermal system characterized by high temperature, high CH4 and very low H2S fluxes. Such characteristics are reflected in potentially great supply of methane for methanotrophs and scarce presence of inhibitors of their activity (H2S and NH3) in the Pantelleria soils. Potential methanotrophic activity within these soils was already evidenced by the CH4/CO2 ratio of the flux measurements which was lower than that of the respective fumarolic manifestations indicating a loss of CH4 during the gas travel towards the earth’s surface. In this study laboratory incubation experiments using soils sampled at Favara Grande, the main hydrothermal area of Pantelleria, showed very high methane consumption rates (up to 9500 ng CH4 h1 g1). Furthermore, microbiological and culture-independent molecular analyses allowed to detect the presence of methanotrophs affiliated to Gamma- and Alpha-Proteobacteria and to the newly discovered acidothermophilic methanotrophs Verrucomicrobia. Culturable methanotrophic Alpha-proteobacteria of the genus Methylocystis were isolated by enrichment cultures. The isolates showed a wide range ...